Obstetric Patient Safety: An Overview - Grobman, William A. (American Journal of Perinatology, 2012)
Patient safety, defined as “the absence of the potential for, or the occurrence of, health care associated injury to the patient,” is a part of the larger concept of health care quality. Achieving safe patient care has become an increasing focus of the obstetric community, in part due to the realization of the number of preventable adverse events that occur as well as the pressures of the professional liability climate. Studies of obstetric care have revealed that multiple factors contribute to the occurrence of adverse obstetric events, although communication is one factor that consistently has been found to prominently contribute to these events. The data that exist also suggest that although most women who give birth on a labor and delivery unit do so without a significant safety incident, a notable minority does experience an event that may compromise their ability to achieve an optimal outcome.
Keywords: obstetrics; patient safety; health care quality; communication